Marine Ecology Biotic and Abiotic Interactions - Türkoğlu, Muhammet; Önal, Umur; Ismen, Ali (IntechOpen, 2018)
During the last decades, aquatic resources have been severely depleted due to human-induced factors such as overexploitation and pollution and more recently due to deviations in the physicochemical parameters of oceans, dramatic changes in weather patterns and melting of glaciers. The effects of these man-made factors are occurring in a relatively shorter time scale and, in many cases, are beyond the capacity of organisms to adapt to these deviations. The majority of natural aquatic resources, which are one of the most important food sources on the planet, are being used to the extent that limits their capacity for regeneration. Despite ongoing attempts towards developing strategies for long-term management of aquatic resources all over the world, efforts have met with limited success. Thus, the sustainable use of aquatic resources has become a very important reality considering a projected human population of 11 billion by the year 2100. With this reality in mind, the purpose of this book is to shed more light on the field of marine ecology by emphasizing the diversity of aquatic life on earth and its importance both as part of a balanced ecosystem and as part of critical source of food on earth. The book covers important findings, discussions and reviews on a variety of subjects on environmental and competitive interactions of marine organisms at different trophic levels and their effects on the productivity, dynamics and structure of marine ecosystems around the world. Each chapter focuses on a specific case in the field of marine ecology and was written by researchers with years of experience in their respective fields. We hope that academicians, researchers and students as well as experts and professionals working in the field of marine ecology will benefit from these contributions. We also hope that this book will inspire more studies to help better understand the marine environment and develop strategies to better protect this crucial element of life on earth.